Kerjasama Indonesia dan Malaysia terhadap penentuan batas Wilayah dalam perspektif Hukum internasional - Dhia Fadlia; St Ulfah; Muhammad Zulkifli Muhdar (Qawanin Jurnal Ilmu Hukum, 2021)
Abstract: This study aims to provide an understanding to related parties regarding theCooperation between Indonesia and Malaysia on the Determination ofTerritorial Boundaries in the Perspective of International Law, first, how isthe international legal arrangement regarding the Cooperation indetermining the territorial boundaries between Indonesia and Malaysia,second, how is the application of international law into national lawconcerning Cooperation in determining regional boundaries. The type ofresearch used is the type of normative research. This study aims to provide anunderstanding of the cooperation between Indonesia and Malaysia on thedetermination of territorial boundaries in the perspective of internationallaw. The results of the study conclude, there are several internationalprovisions in the form of an MOU that has regulated the determination of theboundaries of Indonesia and Malaysia but there are still defaults. The 1945Constitution of the Republic of Indonesia, in article 25A, instructs thegovernment to make laws to determine state boundaries that can be used asguidelines in defending Indonesia's sovereignty. Based on the results of theresearch on Cooperation between Indonesia and Malaysia on thedetermination of state boundaries in the perspective of international law, theresearcher provides advice to the relevant parties based on the problems thatoccur, namely research on the settlement of land boundary disputes betweenIndonesia and Malaysia. Based on the description of the research results, thelegal basis for determining land boundaries and determining sea boundariesbetween Indonesia and Malaysia has been widely implemented and ratified inthe form of laws or presidential decrees, but there are still many Indonesianborder areas that require immediate handling. Abstrak: Penelitian ini bertujuan untuk memberikan pemahaman kepada pihak-pihakterkait mengenai Kerjasama Indonesia dan Malaysia Terhadap PenentuanBatas Wilayah dalam Perspektif Hukum Internasional, pertama,bagaimanakah pengaturan hukum internasional tentang Kerjasamapenentuan batas wilayah antara Indonesia dan Malaysia, kedua,bagaimanakah penerapan hukum internasional kedalam hukum nasionaltentang Kerjasama penentuan batas wilayah. Jenis penelitian yang digunakanadalah jenis penelitian normatif. Penelitian ini bertujuan memberikanpemahaman mengenai Kerjasama Indonesia dan Malaysia terhadappenentuan batas wilayah dalam perspektif hukum internasional. Hasil daripenelitian menyimpulkan, terdapat beberapa ketentuan internasional berupa MOU yang telah mengatur tentang penentuan batas Indonesia dan Malaysianamun masih terdapat wanprestasi. UUD Negara Republik Indonesia tahun1945, dalam pasal 25A memerinrahkan pembuatan UU kepada pemerintahuntuk menentukan batas wilayah negara yang dapat dijadikan pedomandalam mempertahankan kedaulatan Indonesia. Berdasarkan hasil penelitianmengenai Kerjasama Indonesia dan Malaysia terhadap penentuan bataswilayah negara dalam perspektif hukum internasional, peneliti memberikansaran pada pihak-pihak yang terkait berdasarkan permasalahan yangterjadi, yakni penelitian Penyelesaian sengketa batas wilayah darat antaraIndonesia dan Malaysia. Berdasarkan uraian hasil penelitian, Dasar Hukumpenentuan batas wilayah darat dan penentuan batas wilayah laut antaraIndonesia dan Malaysia telah banyak dilakkan dan diratifikasi dalam bentukUndang-Undang atau Kepres, namun masih banyak juga wilayah perbatasanIndonesia yang memerlukan penanganan secepatnya.